Pengaruh Tingkat Pendidikan Terhadap Kemampuan Aparatur Pemerintahan Nagari dalam Pengelolaan Keuangan Nagari - Khairani, Khairani (JESS (Journal of Education on Social Science); Vol 3 No 1 (2019): Relationship between Government and CommunityDO - 10.24036/jess/vol3-iss1/170, 2019)
The purpose of this study was to determine the effect of level education on the performance of nagari apparatus in nagari financial management in Tanah Datar Regency. B ackground of this study was that there were i ndications that the financial management of nagari was still not good in Tanah Datar Regency. This research used  quantitat ive research method . The population of this research was all of the nagari apparatus in Tanah Datar regency numbered 600 people consisting of walinagari , nagari secretaries, nagari treasurer and five head of  nagari affairs. The sample in this research consisted of 24 5 respondents who were determined using the Slovin formula and through the Multi Stage Random Sampling technique. The data w ere collected through questionnaires . D ata of this research were analyzed with Anova Test . The results in this research indicate d no that there was significant difference in the performance of nagari financial management based on education level in Tanah Datar Regency.